2021
DOI: 10.1111/ipd.12780
|View full text |Cite
|
Sign up to set email alerts
|

Does molar‐incisor hypomineralization (MIH) affect only permanent first molars and incisors? New observations on permanent second molars

Abstract: Background:The second permanent molar plays an important role when considering extraction of first permanent molars severely affected by molar-incisor hypomineralization (MIH). Aim: To assess the association between MIH and enamel hypomineralization of the second permanent molars in terms of presence and severity. Design: In this retrospective cross-sectional study, permanent teeth were evaluated in 453 patients between the ages of 13 and 16 at a dental clinic, using intraoral photographs. A calibrated examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 25 publications
4
14
0
Order By: Relevance
“…These findings also help establish a prognosis and plan preventive strategies and monitoring to avoid complex and costly restorative procedures for the patient and those responsible. Besides, they support the results of other studies that have demonstrated the association between MIH and DDE in other permanent teeth (24,25). In terms of severity, de Farias et al reported that mild hypomineralizations in the second permanent molar were more frequent when the first permanent molar presented severe MIH (OR= 4.01; 95% CI: 2.50 7.77) (24).…”
Section: Discussionsupporting
confidence: 84%
“…These findings also help establish a prognosis and plan preventive strategies and monitoring to avoid complex and costly restorative procedures for the patient and those responsible. Besides, they support the results of other studies that have demonstrated the association between MIH and DDE in other permanent teeth (24,25). In terms of severity, de Farias et al reported that mild hypomineralizations in the second permanent molar were more frequent when the first permanent molar presented severe MIH (OR= 4.01; 95% CI: 2.50 7.77) (24).…”
Section: Discussionsupporting
confidence: 84%
“…2 Reports have also indicated that the second primary molars, second permanent molars, and the tips of the permanent canines can be involved. 3 …”
Section: Introductionmentioning
confidence: 99%
“…MIH is a prevalent dental condition that effect up to 25% of children worldwide. 3 Its exact etiology remains uncertain. 1 , 3 In general, enamel hypomineralization is caused by a disturbance in the function of ameloblast cells during any of the amelogenesis stages.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations